(untitled) (Portuguese Journal of Family Medicine and General Practice, 2024)
Luís Augusto Coelho Pisco was born in Porto and studied Medicine in Coimbra. After completing his degree, he went further south, settling at Caldas da Rainha where he reached the top of his career as Head of General and Family Medicine Service at the Foz do Arelho Health Center. He also completed the Occupational Medicine course at the National School of Public Health, obtaining the title of specialist. It is in the West that he still feels proudly rooted and happy today.